Prescribing pattern and adverse drug reactions monitoring in patients with rheumatoid arthritis in a tertiary care hospital - M., Lakshmi Prabha; A., Geetha Rani; Balasubramanian, Meenakshi; J., Ezhil Ramya (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Rheumatoid arthritis is a chronic inflammatory arthritis which requires lifelong treatment to prevent the damage to joints and to maintain day to day functioning of patients. All the drugs used in the treatment of rheumatoid arthritis show significant toxicity and hence it is very important that their use require regular monitoring for adverse reactions. The present study is designed to estimate the prescribing pattern and the occurrence of adverse drug reactions in patients with rheumatoid arthritis. Methods: This prospective observational study was conducted from July 2014 to September 2014 in rheumatology outpatient department.75 patients who fulfilled the study criteria were observed for 3 months. Their prescriptions were collected and analysed. The CSDCO reporting forms were used for the collection of adverse drug reactions. Causality assessment was done by using WHO-UMC scoring system and severity assessment by modified Hartwig and Siegel scale. Results: The study group consists of 85.6 % female. Majority of them were in age group 40-49 years. Average number of drugs per prescription was 4.97.Out of 75 patients, 57.33% were on single DMARD, and 33.33% required 2 DMARDs and 9.33% were prescribed 3 DMARDs. A total of 64 adverse drug reactions were reported out of which 29.6% was due to glucocorticoids, 25% was due to the use of NSAIDS and steroids. Chloroquine maculopathy occurred in 2 patients and elevated liver enzymes occurred in 6 patients due to methotrexate which necessitated DMARD withdrawal. Eight percent of the ADRs were severe. Conclusions: Treatment of rheumatoid arthritis is based on DMARDs and glucocorticoids where it is difficult to prevent the occurrence of ADRs. Consistent monitoring of therapy is needed for early recognition of ADRs and prompt action.